Systematic rim cyano-functionalization of pillar[5]arene and corresponding host–guest property varieties. Issue 18 (24th April 2019) - Wang, Guo; Qiang, Hui; Guo, Yun-Zhe; Yang, Jie; Wen, Ke; Hu, Wei-Bo
Abstract : Synthetic investigation of the systematic replacement of alkoxy groups in pillar[5]arene by cyano ones was carried out. Host–guest property studies of n CN-pillar[5]arenes and 1, 4-dicyanobutane showed the functionization number related host–guest interaction varieties. Abstract : Synthetic investigation of the systematic replacement of alkoxy groups in pillar[5]arene by cyano ones was carried out. 2 n CN-pillar[5]arenes ( n = 1, 2, 3, 4 or 5) bearing different numbers of cyano functions on their rims were successfully prepared for the first time. Single-crystal X-ray diffraction studies showed that the n CN-pillar[5]arenes had unique conformations in the solid states. Besides, host–guest property studies of those n CN-pillar[5]arenes and 1, 4-dicyanobutane showed the functionization number-related host–guest interaction varieties.